INFLUENCE OF TRAINING SPIRITUAL LEADERSHIP AND CLIMATE OF WORKING ON THE EMPLOYEES PERFORMANCE IN OFFICE EDUCATION PROVINCE OF LAMPUNG - Patimah, Siti (Jurnal Pendidikan Islam, 2016)
The leadership and the atmosphere in the working environment within the organization as a manager and leader of an organization have a very big role in creating a conducive and innovative working environment. Therefore, this study investigates leadership and working climate influencing on employee performance of Lampung Provincial Education Office. It uses a quantitative approach and descriptive survey method. Based on data analysis, the results are as follows: first, in general the results of data analysis showed that the leadership, the climate of employee and employee performance Education Office of Lampung Province is categorised as middle/enough, it means that the leadership, work climate and employee performance still need to be improved. Based on the results it can be argued that in order to improve the performance of employees can be done through visionary leadership, hard work, perseverance, steel service and discipline as well as to create a conducive working environment.